2022
DOI: 10.1111/apa.16559
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitators' opinions on using a respiratory function monitor during neonatal resuscitation

Abstract: Aim The aim of this study was to assess the resuscitators' opinions of the usefulness and clinical value of using a respiratory function monitor (RFM) when resuscitating extremely preterm infants with positive pressure ventilation. Methods The link to an online survey was sent to 106 resuscitators from six countries who were involved in a multicentre trial that compared the percentage of inflations within a predefined target range with and without the RFM. The resuscitators were asked to assess the usefulness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…To date, the visual feedback from RFMs has required considerable instruction, time and experience to interpret, as highlighted by incorrect management strategies with inexperienced users 12. Kuypers et al 11 emphasised the need for improved training on RFM interpretation after surveying resuscitators involved in the MONitoR trial,15 suggesting that a simpler visual interface may facilitate interpretation, a sentiment echoed by Schilleman et al 17. In response to this, we chose an RFM with a user-friendly interface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the visual feedback from RFMs has required considerable instruction, time and experience to interpret, as highlighted by incorrect management strategies with inexperienced users 12. Kuypers et al 11 emphasised the need for improved training on RFM interpretation after surveying resuscitators involved in the MONitoR trial,15 suggesting that a simpler visual interface may facilitate interpretation, a sentiment echoed by Schilleman et al 17. In response to this, we chose an RFM with a user-friendly interface.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the visual feedback from RFMs has required considerable instruction, time and experience to interpret, as highlighted by incorrect management strategies with inexperienced users. 12 Kuypers et al 11 emphasised the need for improved training on RFM interpretation after surveying resuscitators involved in the MONitoR trial, 15 suggesting that a simpler visual interface may facilitate interpretation, a sentiment echoed by Schilleman et al 17 In response to this, we chose an RFM with a user-friendly interface. The simplicity of the Monivent's colour-coded visual display, which adopts a traffic light system to depict Vt e , requires minimal training to interpret, as demonstrated by the short (approximately 3 min) training section on monitor interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuyper et al surveyed clinicians using the New Life Box Neo-RSD RFM in a large multicentre trial in preterm infants 24 , 25 . They reported a similarly high level of satisfaction with the RFM: 99% of clinicians reported that the RFM was helpful during resuscitations; 92% reported that it influenced their decision making.…”
Section: Discussionmentioning
confidence: 99%
“…There are now several respiratory function monitoring (RFM) devices available to support ventilation and guide tidal volume delivery. RFM has been shown to reduce mask leak [44][45][46][47], improve tidal volume and positive inspiratory pressure delivery [47][48][49], and is considered by clinicians to be a helpful tool when sufficient training is provided [50,51]. A recent systematic review and meta-analysis identified three RCTs including a total of 442 patients which compared RFM and clinical assessment versus clinical assessment alone [52].…”
Section: Respiratory Function Monitoring (Table 2)mentioning
confidence: 99%